2007
DOI: 10.1021/ma062864w
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the Enhanced Mobility at the Free Surface of Polystyrene:  Fluorescence Studies of the Glass Transition Temperature in Thin Bilayer Films of Immiscible Polymers

Abstract: By selective placement of fluorescent dyes, we have measured the glass transition temperature (T g ) of individual layers within supported bilayer films of different polymers to determine the extent to which strong free-surface effects and substrate interactions are mediated by a narrow interface between immiscible polymers. We have discovered that the impact a free surface has on T g within an ultrathin PS layer is extremely sensitive to the polymer species used in the underlayer. The large T g reduction of ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
246
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(272 citation statements)
references
References 64 publications
18
246
8
Order By: Relevance
“…Measurements of a 14-nm-thick fluorescently labeled PS layer embedded in a thick PS layer 8 showed that the enhanced mobility inherent in the free-surface region can propagate into the interior of the film as deep as 20-30 nm, which is much longer than the length scale of a single cooperatively rearranging region reported for bulk PS (B3.5 nm); 30 once the mobility of segments in the topmost surface layer is enhanced, it would yield a series of perturbations toward the adjacent interior layer, leading a dynamics perturbation into the interfacial layer. 8,31,32 It is thus quite likely that in ultrathin films under such ultraslow temperature variation, the enhanced mobility in the surface region can slowly propagate into the interfacial layer via the interior layer, until it finally modifies local dynamics of the interfacial layer. Once substantially slower dynamics near the substrate are activated by the perturbation of cooperative dynamics originating in the surface layer under such ultraslow rates, the spatial variation in averaged dynamics across the film might become small enough to give rise to a narrowing of the glass transition.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of a 14-nm-thick fluorescently labeled PS layer embedded in a thick PS layer 8 showed that the enhanced mobility inherent in the free-surface region can propagate into the interior of the film as deep as 20-30 nm, which is much longer than the length scale of a single cooperatively rearranging region reported for bulk PS (B3.5 nm); 30 once the mobility of segments in the topmost surface layer is enhanced, it would yield a series of perturbations toward the adjacent interior layer, leading a dynamics perturbation into the interfacial layer. 8,31,32 It is thus quite likely that in ultrathin films under such ultraslow temperature variation, the enhanced mobility in the surface region can slowly propagate into the interfacial layer via the interior layer, until it finally modifies local dynamics of the interfacial layer. Once substantially slower dynamics near the substrate are activated by the perturbation of cooperative dynamics originating in the surface layer under such ultraslow rates, the spatial variation in averaged dynamics across the film might become small enough to give rise to a narrowing of the glass transition.…”
Section: Discussionmentioning
confidence: 99%
“…Multilayer film experiments by Torkelson and co-workers have shown that a given layer of the multilayer film may have different T g depending on the properties of neighboring layers. 27 Here, we emphasize that changes in dynamics do not necessarily arise from the substrate interaction strength alone; changes in the rigidity of the interface (e.g., polymer films placed on a polymer substrate with the same substrate interaction strength but having different molecular flexibilities) and substrate roughness are also relevant.…”
Section: A Survey Of Substrate Interaction and Rigidity Effectsmentioning
confidence: 99%
“…Torkelson et al have taken advantage of this capability by monitoring the T g in patterned [9] and multilayered [16,17,33] films. In the multilayered films, thin layers of polymer chains labeled or doped with aromatic fluorophores were spin-coated on top of or between layers of polymer films to determine the transition in systems with different polymerepolymer interactions or at different depths within a certain polymer.…”
Section: Introductionmentioning
confidence: 99%